Implementasi Perda Nomor 2 Tahun 2010 tentang Larangan Peredaran Minuman Beralkohol di Kota Serang - Supriatinengsih, Anisa; Riswanda, Riswanda (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The problem of alcohol abuse, which has serious health and social impacts, has become a crucial issue in Serang City. This study aims to analyze the implementation of the policy prohibiting the distribution of alcoholic beverages in Serang City based on Regional Regulation Number 2 of 2010 concerning the Prevention, Eradication, and Management of Community Diseases. This research is motivated by the still widespread practice of selling alcoholic beverages underground, especially in herbal medicine stalls. This study uses a qualitative method with a descriptive approach, as well as the public policy implementation theory from Van Meter and Van Horn, which emphasizes Data obtained through observation, structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the policy prohibiting the distribution of alcoholic beverages in Serang City is not optimal. Despite having a strong legal basis and government commitment, its implementation is still hampered by weak coordination, limited resources, and a lack of socialization. The Public Order Agency (Satpol PP) is the main implementer, but has not received synergistic support from other agencies. In addition, socio-cultural and religious factors also influence public perception, resulting in a gap between policy objectives and field reality. Researchers recommend increased inter-agency coordination, public education, and a more adaptive policy approach to social diversity.